2014
DOI: 10.1021/ie5025529
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Die Geometry on Fiber Motion and Fiber Attenuation in the Melt-Blowing Process

Abstract: Melt blowing is a technology for producing microfibrous nonwovens. The melt-blowing die is the key component of the melt-blowing device. In this study, a slot die and a swirl die were used to study the effects of die geometry on fiber motion and fiber attenuation in the melt-blowing process. The fiber paths in these two melt-blowing processes were recorded dynamically with a high-speed camera at a shutter speed of 3000 frames per second. The fiber path profiles, especially the whipping behavior, were for the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 22 publications
0
25
0
1
Order By: Relevance
“…It is accessible that air with higher velocity can provide stronger attenuation of fiber and air with higher temperature can maintain molten status of fiber in longer time. However, Xie and Zeng [32] showed that higher air velocity and higher air temperature not always produced fibers with smaller diameter. In their work, a gauge air pressure of 1.0 atm created initial air velocities about 300 and 150 m s -1 for slot-die and swirl-die melt blowing; however, the fibers collected at 25-mm distance below the die have a mean diameter of 75.2 lm for the slot die, and 58.3 lm for the swirl die, for the reason that the type of turbulence also determines attenuating ratio of fiber.…”
Section: Mean Velocity and Temperature Profilesmentioning
confidence: 96%
“…It is accessible that air with higher velocity can provide stronger attenuation of fiber and air with higher temperature can maintain molten status of fiber in longer time. However, Xie and Zeng [32] showed that higher air velocity and higher air temperature not always produced fibers with smaller diameter. In their work, a gauge air pressure of 1.0 atm created initial air velocities about 300 and 150 m s -1 for slot-die and swirl-die melt blowing; however, the fibers collected at 25-mm distance below the die have a mean diameter of 75.2 lm for the slot die, and 58.3 lm for the swirl die, for the reason that the type of turbulence also determines attenuating ratio of fiber.…”
Section: Mean Velocity and Temperature Profilesmentioning
confidence: 96%
“…Typical change in fiber diameter (expressed here as the ratio of die to final fiber diameter), is between 250 (from 0.4 mm down to 1.6 m [16]) and 667 (0.2 mm down to 300 nm [18]) for isotactic polypropylenes. It was reported that the highest fiber diameter reduction occurs at very small post die distances (typically between 10 and 20 mm) and very short times (0.05 ms) [19,20,21,22]. During fiber attenuation, very high extensional strain rates (∼10 6 s -1 ) are achieved [23].…”
Section: Meltblown Technologymentioning
confidence: 99%
“…PLEASE CITE THIS ARTICLE AS DOI:10.1063/1.5116336 FIGURE 9: 3D fiber spiral motion, images size is s 26.3 mm × 45 mm). Reprinted with permission from [22]. Copyright 2014, American Chemical Society.…”
Section: Please Cite This Article Asmentioning
confidence: 99%
“…A temperature too high may cause sticking of the molten fibers (Figure 4). 47 The fiber attenuation significantly depends on the air velocity (air pressure or airflow rate). Figure 3C shows the change in the average fiber diameter and confidence interval with increasing air pressure.…”
Section: Tensile Testmentioning
confidence: 99%